KECERDASAN EMOSIONAL SEBAGAI PEMODERASI PENGARUH KOMPETENSI, INDEPENDENSI DAN KETIDAKJELASAN PERAN TERHADAP KINERJA AUDITOR (Studi Empiris Pada Kantor BPK RI Perwakilan Provinsi Riau) - Salsabila Nadia; Hardi Hardi; Ilham Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to determine the effect of competence and independence and roleambiguity with emotional intelligence as moderating the auditor's performance in theOffice of the Republic of Indonesia BPK Representative of Riau Province. The samplingtechnique used in this study is a saturated sample technique with saturated samplemethod with the number of samples obtained as much as 32 samples. The data collectionmethod used in this study is to distribute questionnaires to auditors at the Office of theRepublic of Indonesia BPK Representative of Riau Province. The data analysis techniqueused in this study is the Moderated Regression Analysis (MRA). Based on the results ofthe research obtained, it shows that emotional intelligence, competence andindependence, and role ambiguity influence auditor performanceKeywords : Kompetence, Independence, Role Ambiguity, Emotional Intelligence andPerformance of Auditors.